Analisis strategi pemasaran untuk meningkatkan penjualan pada toko XYZ - Nurpratama, Mohamad Reza; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Irawan, Rini Larasati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study is to find out the strategy carried out by the XYZ Store in order to increase sales of its clothing products, where this is to get customer satisfaction and profit from sales that have been made, the output of the seller will get increased sales of clothing in the form of shirts, pants, and jackets which has a large size. This study qualitative research. The type of research used is the descriptive method, the object of research is one store that is in e-commerce which is a large-sized clothing store. The result showed that the 7P marketing mix became the basis for XYZ Stores to market its clothes to satisfy consumers. Based on the SWOT matrix that has been carried out, described through SO, Consumers can make clothes according to the basic materials and models they want. WO because the price of cloth is unpredictable, so sometimes the seller doesn’t get too big a profit. ST in the form of advertising prices found in e-commerce. WT, in the form of an order in a certain amount, will get an attractive discount from XYZ Store.